2010
DOI: 10.1002/ajmg.a.33626
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel FMR1 variants by massively parallel sequencing in developmentally delayed males

Abstract: Fragile X syndrome (FXS), the most common inherited form of developmental delay, is typically caused by CGG-repeat expansion in FMR1. However, little attention has been paid to sequence variants in FMR1. Through the use of pooled-template massively parallel sequencing, we identified 130 novel FMR1 sequence variants in a population of 963 developmentally delayed males without CGG-repeat expansion mutations. Among these, we identified a novel missense change, p.R138Q, which alters a conserved residue in the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
106
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 63 publications
2
106
0
1
Order By: Relevance
“…15,16 However, other loss-of-function mutations, including deletions, missense mutations and splice-site mutations, have been reported. [17][18][19][20] The case described here has an 86-kb microduplication that only encompasses the FMR1 and ASFMR1 genes. The ASFMR1 gene promoter is located within intron 2 of the FMR1 gene.…”
Section: Discussionmentioning
confidence: 95%
“…15,16 However, other loss-of-function mutations, including deletions, missense mutations and splice-site mutations, have been reported. [17][18][19][20] The case described here has an 86-kb microduplication that only encompasses the FMR1 and ASFMR1 genes. The ASFMR1 gene promoter is located within intron 2 of the FMR1 gene.…”
Section: Discussionmentioning
confidence: 95%
“…FMRP is an RNA binding protein that serves as a critical regulator of experience-dependent translation in neurons (8). Loss of FMRP perturbs experience-dependent plasticity and results in the autism-related disorder Fragile X syndrome (FXS) (8)(9)(10)(11)(12)(13). In addition to its role in the somatodendritic compartment, FMRP also associates with a distinct granule termed the FXG (Fragile X granule).…”
Section: Introductionmentioning
confidence: 99%
“…This gene does not appear any less mutable than other typical X-linked genes. A recent study sequencing FMR1 in 963 developmentally delayed males observed five silent (synonymous) sites and two replacement (nonsynonymous) sites, 19 which compares favorably with X-linked genome-wide averages of B3.7 silent sites and 2.5 replacement sites. 20 However, if one examines other X-linked monogenic causes of intellectual disability and/or developmental delay (ID/DD), the small number of FMR1 missense mutations is striking.…”
Section: Discussionmentioning
confidence: 85%